A Political Companion to Flannery O'Connor - Edmondson, Henry T., 1955- (Political companions to great American authors., 2017)
Acclaimed author and Catholic thinker Flannery O'Connor (1925-1964) penned two novels, two collections of short stories, various essays, and numerous book reviews over the course of her life. Her work continues to fascinate, perplex, and inspire new generations of readers and poses important questions about human nature, ethics, social change, equality, and justice. Although political philosophy was not O'Connor's pursuit, her writings frequently address themes that are not only crucial to American life and culture, but also offer valuable insight into the interplay between fiction and politics. A Political Companion to Flannery O'Connor explores the author's fiction, prose, and correspondence to reveal her central ideas about political thought in America. The contributors address topics such as O'Connor's affinity with writers and philosophers including Eric Voegelin, Edith Stein, Russell Kirk, and the Agrarians; her attitudes toward the civil rights movement; and her thoughts on controversies over eugenics. Other essays in the volume focus on O'Connor's influences, the principles underlying her fiction, and the value of her work for understanding contemporary intellectual life and culture. Examining the political context of O'Connor's life and her responses to the critical events and controversies of her time, this collection offers meaningful interpretations of the political significance of this influential writer's work.